Anatomy of the proximal tibiofibular joint and interosseous membrane, and their contributions to joint kinematics in below‐knee amputations. Issue 2 (2nd December 2014) - Burkhart, Timothy A.; Asa, Benjamin; Payne, Michael W. C.; Johnson, Marjorie; Dunning, Cynthia E.; Wilson, Timothy D.
Abstract A result of below‐knee amputations (BKAs) is abnormal motion that occurs about the proximal tibiofibular joint (PTFJ). While it is known that joint morphology may play a role in joint kinematics, this is not well understood with respect to the PTFJ. Therefore, the purposes of this study were: (i) to characterize the anatomy of the PTFJ and statistically analyze the relationships within the joint; and (ii) to determine the relationships between the PTFJ characteristics and the degree of movement of the fibula in BKAs. The PTFJ was characterized in 40 embalmed specimens disarticulated at the knee, and amputated through the mid‐tibia and fibula. Four metrics were measured: inclination angle (angle at which the fibula articulates with the tibia); tibial and fibular articular surface areas; articular surface concavity and shape. The specimens were mechanically tested by applying a load through the biceps femoris tendon, and the degree of motion about the tibiofibular joint was measured. Regression analyses were performed to determine the relationships between the different PTFJ characteristics and the magnitude of fibular abduction. Finally, Pearson correlation analyses were performed on inclination angle and surface area vs. fibular kinematics. The inclination angle measured on the fibula was significantly greater than that measured on the tibia. This difference may be attributed to differences in concavity of the tibial and fibular surfaces. Surface area measured on the tibia and fibula was not statistically different. The inclination angle was not statistically correlated to surface area. However, when correlating fibular kinematics in BKAs, inclination angle was positively correlated to the degree of fibular abduction, whereas surface area was negatively correlated. The characteristics of the PTFJ dictate the amount of fibular movement, specifically, fibular abduction in BKAs. Predicting BKA complications based on PTFJ characteristics can lead to recommendations in treatment.